CD8+ tumour-infiltrating lymphocytes in relation to HPV status and clinical outcome in patients with head and neck cancer after postoperative chemoradiotherapy: A multicentre study of the German cancer consortium radiation oncology group (DKTK-ROG) - Balermpas, Panagiotis; Roedel, Franz; Roedel, Claus; Krause, Mechthild; Linge, Annett; Lohaus, Fabian; Baumann, Michael; Tinhofer, Inge; Budach, Volker; Gkika, Eleni; Stuschke, Martin; Avlar, Melanie; et al. (International Journal of Cancer, 2016)
We examined the prognostic value of tumour-infiltrating lymphocytes (TILs) in patients with squamous cell carcinoma of the head and neck (SCCHN) after surgery and postoperative cisplatin-based chemoradiotherapy. FFPE-tissue originating from the surgery of 161 patients treated in 8 DKTK partner sites was immunohistochemically stained for CD3 and CD8. Their expression was correlated with clinicopathological characteristics as well as overall survival (OS), local progression-free survival (LPFS) and distant metastases free-survival (DMFS), also in the context of the HPV16-DNA/p16 status. After a median follow-up of 48 months (range: 4100 months), OS at 4 years was 46.5% for the entire cohort. In multivariate analysis, high CD8 expression was confirmed as an independent prognostic parameter for OS (p=0.002), LPFS (p=0.004) and DMFS (p=0.006), while CD3 expression lacked significance. In multivariate analysis HPV16 DNA positivity was associated with improved OS (p=0.025) and LPFS (p=0.013) and p16-positive patients showed improved DMFS (p=0.008). Interestingly, high CD8 expression was a prognostic parameter for the clinical outcome in both HPV16 DNA-positive and HPV16 DNA-negative patients. Similar findings were observed in the multivariate analysis for the combined HPV16 DNA/p16 status. Altogether, CD8+ TILs constitute an independent prognostic marker in SCCHN patients treated with adjuvant chemoradiotherapy. These data indicate that CD8-positive TILs have antitumour activity and could be used for treatment stratification. Further validation of the prognostic value of CD8+ TILs as a biomarker and its role in the immune response in SCCHN patients after adjuvant chemoradiotherapy is warranted and will be performed in the prospective DKTK-ROG study. What's New? Squamous cell carcinomas of the head and neck (SCCHN) are not a homogenous group of tumors. This means that biomarkers are urgently needed, so that prognosis and treatment can be individualised. In this study, the authors found that patients with higher levels of CD8+ tumor-infiltrating lymphocytes (TILs) within their tumors had improved outcomes after treatment. These results suggest that CD8-positive TILs may have antitumor activity, and that their expression may be a useful prognostic biomarker for treatment stratification. Squamous cell carcinoma of the head and neck (SCCHN) represents about 6% of the total cancer incidence and approximately 500,000 new cases are diagnosed each year worldwide. Radical surgery including resection of the primary tumour and neck dissection of regional lymph nodes followed by postoperative chemoradiotherapy (CRT) is commonly performed in locally advanced SCCHN with a 5-year survival rate of 40-60%.
CRIS-Team Scopus Importer:2023-03-08
Keywords: CD8; DKTK-ROG; HPV; postoperative chemoradiotherapy; prognostic; SCCHN